2017
DOI: 10.1089/zeb.2016.1283
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Comparison ofHoplias malabaricus(Bloch, 1794) (Characiformes, Erythrinidae) in Central Amazon

Abstract: Hoplias malabaricus comprises seven karyomorphs (A-G) and evolutionary units have been described in some of them. In this study, the karyotypic composition and genomic organization of individual H. malabaricus from Central Amazon are described and to verify whether they can be classified according to known karyomorphs. Individuals from the Ducke Reserve have 2n = 42 chromosomes, similar to karyomorph A. Individuals from Catalão Lake and Marchantaria Island exhibit 2n = 40 chromosomes, similar to karyomorph C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…However, we did not find karyomorph F, which is similar to karyomorph C, except for the presence of a metacentric pair, the first in the karyotype (Bertollo et al 2000). Furthermore, variations can be found in the same karyomorph, as reported for karyomorph A from the upper Paraná River basin (Blanco et al 2010), and karyomorphs A and C from the Central Amazon (Guimarães et al 2017). Taken together, all previous evidence indicates that this species group is characterized by very high levels of cytogenetic and molecular variation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…However, we did not find karyomorph F, which is similar to karyomorph C, except for the presence of a metacentric pair, the first in the karyotype (Bertollo et al 2000). Furthermore, variations can be found in the same karyomorph, as reported for karyomorph A from the upper Paraná River basin (Blanco et al 2010), and karyomorphs A and C from the Central Amazon (Guimarães et al 2017). Taken together, all previous evidence indicates that this species group is characterized by very high levels of cytogenetic and molecular variation.…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, we observed a division between populations and karyomorphs (2n = 40 and 2n = 42), suggesting that karyotypic variation in H. malabaricus is a consequence of different chromosomal rearrangements occurring independently in different areas of the distribution range of the species. Guimarães et al (2017) compared two populations of karyomorph A, and found differences related to centromere position, number and location of nucleolar organizer regions (NORs), and organization patterns of heterochromatic regions, demonstrating that evolutionary divergence has occurred within these groups to some degree. This karyotypic pattern is supported by the sedentary habit of H. malabaricus, which may result in restricted gene flow (Dergam et al 2002;Blanco et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…amazonum is also different from the patterns described by Gindri (2009) and Fernandes et al (2015), with a much larger quantity of heterochromatin found in the former one. These differences may be associated with environmental factors, given that different environmental stressors may mediate epigenetic processes of heterochromatin regulation, although it seems more likely that these differences are related to the lack of migration in these species, which favors the accumulation of differential sequences in isolated populations (Guimarães et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fully heterochromatic short arms in submetacentric and subtelocentric chromosomes was also observed in other representatives of the family, such as in the species Serrasalmus (Nakayama et al, 2002) and Myloplus (Favarato et al, 2021). This characteristic must have arisen due to in tandem duplication, especially in association with repetitive DNA elements, since the repetitive nature of these elements seems to be the trigger and target for heterochromatinization (Guimarães et al, 2016;Pinheiro et al, 2016).…”
Section: Discussionmentioning
confidence: 72%